The Effect Of Wave Length And Amplitude on The Hydrodynamic Characteristics of Waste Collection Vessels Using Computational Fluid Dynamics (CFD) - Erik Sugianto; Hadi Prasutiyon; Arif Winarno; Muhammad Khasroni Hamsah (Institut Teknologi Sepuluh Nopember, 2023)
The continuous flow of marine debris in the sea has been a problem until now. Previous research on garbage collection vessels was conducted in calm water conditions, without waves and waves due to wind. This is different from the real conditions in the sea which are choppy and bumpy. In addition, research on the effect of wave length and amplitude on marine debris collection on garbage collection vessels does not yet exist. This study aims to determine the effect of wave length and amplitude on velocity contours, flow patterns, and ship resistance. The ship uses a circular hollow wing conveyor. Modelling using Rhinocheros software, then numerical simulation using Computational Fluid Dynamic (CFD). Verification of the simulation process uses grid independent by varying the mesh size, then validation of the results is done by comparing with previous experimental research. The results show that the best velocity contour in front of the conveyor is at a ship speed of 1.028 m/s (2 knots) using an amplitude of 0.5 T and a wavelength of 0.5 L. The velocity value in front of the conveyor is 1.551 m/s. This affects the speed of collecting marine debris. This affects the speed of collecting marine debris. The model that has a laminar flow pattern at the bow and at the stern is a speed of 1 knot at an amplitude variation of 0.1 T and a wavelength of 0.1 L. This is the best because it is easy to collect garbage. The smallest drag is the speed of 0.514 m/s (1 knot) at amplitude variation of 0.1 T and wavelength of 0.1 L. At this condition, the fuel consumption is the least. Thus, the greater the wavelength and amplitude of the waves the greater the drag and the smaller the speed.